Comparative study of chloroplast genomes across seven Salacca species - ARSLAN ARSHAD; REDI ADITAMA; MEGAYANI SRI RAHAYU; AZIS NATAWIJAYA; DEDEN DERADJAT MATRA; SUDARSONO SUDARSONO (Society for Indonesian Biodiversity, 2024)
Abstract. Arshad A, Aditama R, Rahayu MS, Natawijaya A, Matra DD, Sudarsono S. 2024. Comparative study of chloroplast genomes across seven Salacca species. Biodiversitas 25: 4043-4058. Chloroplast (Cp) genomes play a vital role in comprehending plant evolution, biodiversity, and phylogenetics. Snake fruit is a tropical fruit in the Indo-Malayan region. This work compares seven Salacca species Cp genomes to clarify their genetics and evolutionary connections. Cp genomes were constructed using sequencing data from the BGISeq-500 platform and the GetOrganelle assemblers. The assembled Cp genomes have a standard four-part structure and vary in length from 157,047 to 158,182 kilobase pairs (kbp). Comparative genomics analysis found the ycf1 gene to have the highest number of single nucleotide polymorphisms (SNPs), revealing missing amino acids in Salacca affinis. The Cp genomes showed a high prevalence of mononucleotide SSR motifs. With a few exceptions, especially Salacca wallichiana, most Cp genomes showed stable borders between the large single copy (LSC), inverted repeat (IR), and short single copy (SSC) sections. This research underscores the importance of Cp genome information for identifying species, a crucial tool for evolutionary studies and breeding purposes. Furthermore, it emphasizes the intimate genetic connection between Salacca and Cocos nucifera, which contrasts with Phoenix dactylifera. This thorough research provides vital insights into the genetics of Salacca species and highlights the usefulness of Cp genome data in subsequent analyses.